Poly(Acrylic Acid-b-Styrene) Amphiphilic Multiblock Copolymers as Building Blocks for the Assembly of Discrete Nanoparticles - Greene, Anna C. (2011)
In order to expand the utility of current polymeric micellar systems, we have developed amphiphilic multiblock copolymers containing alternating blocks of poly(acrylic acid) and poly(styrene). Heterotelechelic poly(tert-butyl acrylate-b-styrene) diblock copolymers containing an α-alkyne and an ω-azide were synthesized by atom transfer radical polymerization (ATRP), allowing control over the molecular weight while maintaining narrow polydispersity indices. The multiblock copolymers were constructed by copper-catalyzed azide-alkyne cycloaddition of azide-alkyne end functional diblock copolymers which were then characterized by (1)H NMR, FT-IR and SEC. The tert-butyl moieties of the poly(tert-butyl acrylate-b-styrene) multiblock copolymers were easily removed to form the poly(acrylic acid-b-styrene) multiblock copolymer ((PAA-PS)(9)), which contained up to 9 diblock repeats. The amphiphilic multiblock (PAA-PS)(9) (M(n) = 73.3 kg/mol) was self-assembled by dissolution into tetrahydrofuran and extensive dialysis against deionized water for 4 days. The critical micelle concentration (CMC) for (PAA-PS)(9) was determined by fluorescence spectroscopy using pyrene as a fluorescent probe and was found to be very low at 2 × 10(-4) mg/mL. The (PAA-PS)(9) multiblock was also analyzed by dynamic light scattering (DLS) and transmission electron microscopy (TEM). The hydrodynamic diameter of the particles was found to be 11 nm. Discrete spherical particles were observed by TEM with an average particle diameter of 14 nm. The poly(acrylic acid) periphery of the spherical particles should allow for future conjugation of biomolecules.